Testing the Multiproduct Hypothesis on Norwegian Aluminium Industry Plants - Jan Larsson (Statistics Norway, Research Department, 2003)
Although most production activities involve multiple outputs, econometric models of production or cost functions normally involve only one single homogeneous output. The aim of this paper is to test the hypothesis that a multiproduct specification is superior to a model with a single homogenous product. To do this, we use a Multiproduct Symmetric Generalized McFadden (MSGM) cost function. This functional form is globally concave and flexible in the sense that it provides a second order differentiable approximation of any arbitrary cost function which is twice continuously differentiable and linear homogenous in input prices. In an empirical application on a panel data from ten Norwegian primary aluminium plants, we find support for our hypothesis. We present estimates of price elasticities, returns to scale and scope, and product specific demand elasticities. Our results indicate economies of scope, i.e. it is more profitable to produce more than one output, and show sensitivity of factor demand when the product mix changes.
Keywords: C33; D21; L61; 330; Cost function; Multiple output; Global concavity; Returns to scale; Economies of scope; Price elasticity; Output elasticity; Panel data; Primary aluminium industry